Risk factors for cerebrovascular disease and stroke - Seshadri, Sudha; Debette, Stéphanie (Oxford University Press, 2016)
This text, by leading stroke researchers from Europe and North America, describes environmental and genetic risk factors for cerebrovascular disease. The section on genetics is exceptionally detailed and contemporaneous.